Fish quality and market performance: The case of the coastal fishery for Atlantic cod in Norway - Sogn-Grundvåg, Geir; Zhang, Dengjun; Henriksen, Edgar; Joensen, Sjúrður; Bendiksen, Bjørn Inge; Hermansen, Øystein (Marine Policy, 2021)
This study focuses on fish quality and resource utilization at the ex-vessel level of the value chain. Substantial waste in the form of reduced fish quality is revealed for Atlantic cod landed by the coastal fleet in Norway, with approximately 30% of the sampled cod from 399 catches downgraded, implying reduced value of products in onshore processing. By using an objective quality index for individual catches in hedonic price modeling, we obtain new insights regarding the important role markets may play in sustainable utilization of marine resources. The econometric results indicate that the quality index had a rather modest effect on prices and that fishing methods is more important in price formation. These findings are attributed to a poorly performing ex-vessel market where asymmetric information regarding fish quality and the bargaining power of fishers distort the relationship between quality and price, with the result that fishers are not incentivized to deliver fish of good quality.